Isoenzymes and dry matter content in wild potato - Rocha, Beatriz Helena Gomes; Augustin, Eliane; da Silva, João Baptista; Pereira, Arione da Silva (Pesquisa Agropecuaria Brasileira, 2000)
Wild potato clones (Solanum spp.) were analysed for tuber dry matter content, leaf aspartate transaminase and leaf isocitrate dehydrogenase isoenzymes in order to identify association between these characteristics. The results indicate that there is great variability for dry matter content among 50 clones analysed. S. commersonii malmeanum clones had higher dry matter levels than S. commersonii commersonii, S. chacoense muelleri and the clones whose species were not identified. Fifteen aspartate transaminase and seven isocitrate dehydrogenase bands were observed in the gels of 38 clones. Tests of χ2, using 2 x 2 contingency table, revealed a significant association between dry matter content and the bands of relative mobility 1.00 of both aspartate transaminase and isocitrate dehydrogenase isoenzymes.